Supervisory Function of Prosecution Service as an Object of Historic and Legal Analysis - SUGAIPOVA, Elina Akhmedovna; HASIEVICH, Movlad Geldibaev (Journal of Advanced Research in Law and Economics; Vol 7 No 8 (2016): JARLE Volume VII, Issue 8(22), Winter 2016, 2017)
The research analyses the emerging supervisory institutes and touches historic prerequisites for the development of supervisory function of the Russian prosecution service.